Treatments that generate higher number of adverse drug reactions and their symptoms - Lucía Fernández-López; Javier Navarro-Zaragoza; María Falcón; Aurelio Luna (Facultad de Farmacia, Universidad de Granada, 2015)
Objectives: Adverse drug reactions (ADRs) are an important cause of morbidity and mortality worldwide and generate high health costs. Therefore, the aims of this study were to determine the treatments which produce more ADRs in general population and the main symptoms they generate. Methods: An observational, cross-sectional study consisting in performing a self-rated questionnaire was carried out. 510 patients were asked about the treatments, illnesses and ADRs, they had suffered from. Results: 26.7% of patients had suffered from some ADR. Classifying patients according to the type of prescribed treatment and studying the number of ADR that they had, we obtained significant differences (p ≤ 0.05) for treatments against arthrosis, anemia and nervous disorders (anxiety, depression, insomnia). Moreover, determining absolute frequencies of these ADRs appearance in each treatment, higher frequencies were again for drugs against arthrosis (22.6% of patients treated for arthrosis suffered some ADR), anemia (14.28%), nerve disorders (13.44%) and also asthma (16%). Regarding the symptoms produced by ADRs, the most frequent were gastrointestinal (60% of patients who suffered an ADR, had gastrointestinal symptoms) and nervous alterations (dizziness, headache, sleep disturbances etc) (24.6%). Conclusion: Therapeutic groups which produce more commonly ADRs are those for arthrosis, anemia, nervous disorders and asthma. In addition, symptoms which are generated more frequently are gastrointestinal and nervous problems. This is in accordance with the usual side effects of mentioned treatments. Health professionals should be informed about it, so that they would be more alert about a possible emergence of an ADR in these treatments. They also could provide enough information to empower patients and thus, they probably could detect ADR events. This would facilitate ADR detection and would avoid serious consequences generated to both patients' health and health economics.